Protein misfolding diseases methods and protocols - Gomes, Cláudio M. 1970- (Springer New York, 2019)
This detailed book gathers a broad collection of experimental approaches to assist researchers in setting up different methods to investigate protein conformational disorders. Beginning with a section on assays focusing on biophysical approaches to study protein (mis)folding, the volume continues with sections on cellular and proteostasis assays as well as assays for protein folding correction and recovery, combining methods such as thermal shift assays, in silico improvement of protein solubility, and compound screening, an important area of research as it may open avenues for therapeutic strategies. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips for troubleshooting and avoiding known pitfalls. Authoritative and practical, Protein Misfolding Diseases: Methods and Protocols serves as an ideal guide for researchers seeking to advance our knowledge of protein conformational disorders
Biophysical and Spectroscopic Methods for Monitoring Protein Misfolding and Amyloid Aggregation -- Ultrasensitive RT-QuIC Seed Amplification Assays for Disease-Associated Tau, α-Synuclein, and Prion Aggregates -- Vesicle-Based Assays to Study Membrane Interactions of Amyloid Peptides -- Differential Scanning Fluorimetry and Hydrogen Deuterium Exchange Mass Spectrometry to Monitor the Conformational Dynamics of NBD1 in Cystic Fibrosis -- A Multipronged Method for Unveiling Subtle Structural-Functional Defects of Mutant Chaperone Molecules Causing Human Chaperonopathies -- High-Throughput Microplate-Based Fluorescence Assays for Studying Stochastic Aggregation of Superoxide Dismutase-1 -- Methods for Structural Analysis of Amyloid Fibrils in Misfolding Diseases -- Assays for Light Chain Amyloidosis Formation and Cytotoxicity -- Monitoring Aggregate Clearance and Formation in Cell-Based Assays -- Monitoring Proteome Stress in Live Cells Using HaloTag-Based Fluorogenic Sensor --
- Quantification of Protein Aggregates Using Bimolecular Fluorescence Complementation -- Screening Protein Aggregation in Cells Using Fluorescent Labels Coupled to Flow Cytometry -- Induction of Cu/Zn Superoxide Dismutase (SOD1) Aggregation in Living Cells -- A Cell Model for HSP60 Deficiencies: Modeling Different Levels of Chaperonopathies Leading to Oxidative Stress and Mitochondrial Dysfunction -- Super-Resolution Fluorescence Imaging of Mutant Huntingtin Aggregation in Cells -- Thermal Shift and Stability Assays of Disease-Related Misfolded Proteins Using Differential Scanning Fluorimetry -- Methods to Screen Compounds against Mutant p53 Misfolding and Aggregation for Cancer Therapeutics -- Early Stage Discovery and Validation of Pharmacological Chaperones for the Correction of Protein Misfolding Diseases -- Constructing Kinetically Controlled Denaturation Isotherms of Folded Proteins Using Denaturant-Pulse Chaperonin Binding --
- In Vitro Prion Amplification Methodology for Inhibitor Screening -- SolubiS: Optimizing Protein Solubility by Minimal Point Mutations
Keywords: Proteins